Dual nanocarrier of chlorhexidine and fluconazole: Physicochemical characterization and effects on microcosm biofilms and oral keratinocytes - Araujo, Heitor Ceolin [UNESP]; Pessan, Juliano Pelim [UNESP]; Caldeirão, Anne Caroline Morais; Sampaio, Caio [UNESP]; Oliveira, Marcelo José dos Santos [UNESP]; Sales, Douglas Henrique [UNESP]; Teixeira, Silvio Rainho [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Ramage, Gordon; Monteiro, Douglas Roberto [UNESP] (Elsevier, 2023)
Objectives: This study assembled and characterized a dual nanocarrier of chlorhexidine (CHX) and fluconazole (FLZ), and evaluated its antibiofilm and cytotoxic effects. Methods: CHX and FLZ were added to iron oxide nanoparticles (IONPs) previously coated by chitosan (CS) and characterized by physical-chemical analyses. Biofilms from human saliva supplemented with Candida species were grown (72 h) on glass discs and treated (24 h) with IONPs-CS carrying CHX (at 39, 78, or 156 µg/mL) and FLZ (at 156, 312, or 624 µg/mL) in three growing associations. IONPs and CS alone, and 156 µg/mL CHX + 624 µg/mL FLZ (CHX156-FLZ624) were tested as controls. Next, microbiological analyses were performed. The viability of human oral keratinocytes (NOKsi lineage) was also determined (MTT reduction assay). Data were submitted to ANOVA or Kruskal-Wallis, followed by Fisher's LSD or Tukey's tests (α=0.05). Results: Nanocarriers with spherical-like shape and diameter around 6 nm were assembled, without compromising the crystalline property and stability of IONPs. Nanocarrier at the highest concentrations was the most effective in reducing colony-forming units of Streptococcus mutans, Lactobacillus spp., Candida albicans, and Candida glabrata. The other carriers and CHX156-FLZ624 showed similar antibiofilm effects, and significantly reduced lactic acid production (p<0.001). Also, a dose-dependent cytotoxic effect against oral keratinocytes was observed for the dual nanocarrier. IONPs-CS-CHX-FLZ and CHX-FLZ significantly reduced keratinocyte viability at CHX and FLZ concentrations ≥7.8 and 31.25 µg/mL, respectively (p<0.05). Conclusion: The nanotherapy developed outperformed the effect of the combination CHX-FLZ on microcosm biofilms, without increasing the cytotoxic effect of the antimicrobials administered. Clinical Significance: The dual nanocarrier is a promising topically-applied therapy for the management of oral candidiasis considering that its higher antibiofilm effects allow the use of lower concentrations of antimicrobials than those found in commercial products.
Keywords: Biofilms; Candida; Chlorhexidine; Cytotoxicity; Fluconazole; Iron oxide nanoparticles